Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) terhadap Motivasi dan Hasil Belajar Matematika Siswa Kelas XI TKR SMK Negeri 2 Baubau Tahun Pelajaran 2018/2019 - Rasyid Ebe (Jurnal Akademik FKIP Unidayan, 2020)
Problems in this research are how is (1) learning motivation of grade XI TKR students at SMK Negeri 2 Baubau taught by using cooperative learning model of STAD type, (2)the learning outcomes of grade XI TKR student at SMK Negeri 2 Baubau taught by using cooperative learning model of STAD type, (3) the influence of cooperative learning model of STAD type toward learning motivation of grade XI TKR student at SMK Negeri 2 Baubau, (4) the influence of cooperative learning model of STAD type toward learning outcomes of grade XI TKR student at SMK Negeri 2 Baubau. The reseacrh used quasy experimental design. Research population are the entire students of grade XI TKR of second semester at SMK Negeri 2 Baubau, academic year 2018/2019. The sample are students of grade XI TKR 1 and grade XI TKR 2 consisted of 61 students. Samples chosen through simple random sampling technique. Data obtained by using questionnaire and test. The research result revealed that (1) student’s learning motivation in the control class after the treatment is 90.90 and in very high categories, while in experiment class is 104.16 and in very high categories; (2) students learning outcomes in control class after the treatment is 74.24 and in very high categories,while in experiment class is 83.84and in very high categories; (3) the implementation of cooperative learning model of STAD type give positive influence toward learning motivation and learning outcomes of grade XI TKR students at SMK Negeri 2 Baubau.